ANALISIS KERUGIAN ENERGI SISTEM TURBIN GAS DI PLTGU BLOK III PT. X, CIKARANG, BEKASI - Komarudin Komarudin; Muhammad Rizqi Fauzi Rahman (Bina Teknika, 2017)
Gas Turbine Generator (GTG) 8 operates since January 2010. The problem that occurs from the gas turbine system is decreasing of electrical power. From the commissioning data, GTG 8 is capable of generating 120.2 megawatts of electrical power. In March 2017 GTG 8 was only able to generate electricity by 109.1 megawatts. There was a decrease of 9.23% of electric power capacity. Overview of thermal efficiency and heat loss needs to be done to find out improvement opportunities and recommendations. At commissioning period, thermal efficiency reaches 32.06% while from 2013 to 2017 the average thermal efficiency value reaches only 29.25%. From the data obtained rate of efficiency decreasing 2.81%. At commissioning, the resulting heat loss only reached 135.03 MW. The current operating conditions average heat loss reached 172.50 MW. There was a deviation of 37.47 MW or 21.7%. Based on calculations and data, one factor that can decrease of thermal efficiency and increase heat loss is the compression temperature. The increase in compression temperature is caused by the dust and impurities that enter into the compressor that precipitates on the compressor blades so that the compressed air temperature tends to increase. Dust and impurities can be reduced by the offline water wash method. This process can lower the compression temperature from 693.68 OF to 690.62 OF. A decline of 3.06 OF. This results in actual work of the compressor decreasing from 153.26 Btu / lb to 152.13 Btu / lb. Turbine thermal efficiency tends to increase from 29.02% to 29.43% or increase by 0.41%. After the offline water wash process, the generator generated power reaches 110.50 MW. Increases 4 MW or 3.62% compared to before the compressor is cleaned. The increase causes the system's heat loss to decrease by 5.2 MW or 2.96%.